Determination of optimal quick switching system with varying sample size for assuring mean life under Weibull distribution. Issue 2 (3rd April 2018) - Balamurali, S.; Jeyadurga, P.; Usha, M.
Abstract: Conventional sampling plans are applied to dispose an individual lot or isolated lot that requires a large sample size. Consequently, the inspection time and cost needed to make a decision under conventional plans are high. In order to reduce the sample size and to inspect the series of lots with minimum cost and time, special purpose plans are utilized. In this article, we propose one of the special purpose plans, namely, a quick switching sampling system that is also known as a two-plan sampling system. Through this sampling system, the Weibull-distributed mean life of the product is ensured based on time-truncated life tests. The proposed system is designed with the intention of minimizing the average sample number using two points on the operating characteristic curve approach. The optimal parameters of the proposed system are determined for different combinations of producer's risk and consumer's risk. Implementation of the proposed system is also explained and the performance of the proposed system is compared with other existing plans. In addition, the effects of misspecification of shape parameters on optimal parameters and the probability of acceptance are discussed.